2004
DOI: 10.1002/chem.200400596
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of a Selenenyl Fluoride ArSeF by NMR Spectroscopy: The Nature of Ar2Se2/XeF2 and ArSeSiMe3/XeF2 Reagents

Abstract: Arylselenenyl fluorides ArSeF are obtained from diselenides Ar2Se2 or arylselenotrimethylsilanes ArSe-SiMe3, and XeF2. They are detected by low-temperature 19F and 77Se NMR spectroscopy. Substitution in the ortho position of the aromatic ring to provide electronic or steric protection is a requirement for their formation. ArSe--F compounds decompose according to 3 ArSe-F-->[ArSe-SeF2Ar]+ArSe-F-->ArSeF3+Ar2Se2. Reaction energies for this disproportionation as well as that of the sulfur and tellurium homologues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
2
12

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 92 publications
1
51
2
12
Order By: Relevance
“…The dealkylation reaction leading to the same cation was also achieved by treatment of the above selenides with bromine. Later on, Poleschner and Seppelt 18 reported that reaction of [2,6- 6 ] into the same ionic species described by Furukawa. Recently, an X-ray diffraction study revealed the ionic nature of the organoselenium(II) bromide [{2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Se] + -Br − ·H 2 O. The crystal contains dimers featuring two bromide anions, two cations, and two water molecules connected through Br⋯Se and Br⋯H interactions.…”
Section: Introductionmentioning
confidence: 66%
“…The dealkylation reaction leading to the same cation was also achieved by treatment of the above selenides with bromine. Later on, Poleschner and Seppelt 18 reported that reaction of [2,6- 6 ] into the same ionic species described by Furukawa. Recently, an X-ray diffraction study revealed the ionic nature of the organoselenium(II) bromide [{2,6-(Me 2 NCH 2 ) 2 C 6 H 3 }Se] + -Br − ·H 2 O. The crystal contains dimers featuring two bromide anions, two cations, and two water molecules connected through Br⋯Se and Br⋯H interactions.…”
Section: Introductionmentioning
confidence: 66%
“…Wir haben Arylselenmonofluoride, ArSeF, sowohl durch sterischen Schutz (Ar = 2,4,6-Tri-tertbutylphenyl = Supermesityl, Mes*) als auch durch intramolekulare Koordination mit Aminogruppen [9] (Ar = 2-Me 2 NCH 2 C 6 H 4 ) stabilisiert und deren Existenz erstmals NMR-spektroskopisch nachgewiesen. [10] Die Experimente, gestützt durch quantenchemische Rechnungen, zeigen, dass nicht-stabilisierte RSeF, wahrscheinlich über RSeF 2 ÀSeR, in einer reversiblen Gleichgewichtsreaktion zu den Diseleniden R 2 Se 2 und Organoselentrifluoriden RSeF 3 disproportionieren. [10,11] Tellurenylfluoride, ArTeF, wurden als monomeres 2-Me 2 NCH 2 C 6 H 4 TeF NMR-spektroskopisch in Lçsung beobachtet, [12] während kürzlich eine Arbeit über das Dimer BbtTeF 2 -TeBbt mit der sperrigen 2,6-Bis[bis(trimethylsilyl)methyl]-4-[tris(trimethylsilyl)methyl]phenyl-Gruppe (Bbt) erschienen ist.…”
Section: In Memoriam Reiner Radegliaunclassified
“…[10] Die Experimente, gestützt durch quantenchemische Rechnungen, zeigen, dass nicht-stabilisierte RSeF, wahrscheinlich über RSeF 2 ÀSeR, in einer reversiblen Gleichgewichtsreaktion zu den Diseleniden R 2 Se 2 und Organoselentrifluoriden RSeF 3 disproportionieren. [10,11] Tellurenylfluoride, ArTeF, wurden als monomeres 2-Me 2 NCH 2 C 6 H 4 TeF NMR-spektroskopisch in Lçsung beobachtet, [12] während kürzlich eine Arbeit über das Dimer BbtTeF 2 -TeBbt mit der sperrigen 2,6-Bis[bis(trimethylsilyl)methyl]-4-[tris(trimethylsilyl)methyl]phenyl-Gruppe (Bbt) erschienen ist. [13] Ziel unserer bereits 2005 begonnenen Untersuchung war es, durch noch grçßere sterische Schutzgruppen als Mes*, RSeF und eventuell auch RTeF in reiner, kristalliner Form zu isolieren.…”
Section: In Memoriam Reiner Radegliaunclassified
See 2 more Smart Citations